Teachers’ Roles in Remote English Teaching at SMA N 1 Tegallalang - Gayatri, Ni Nyoman Tri (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aimed to determine the teacher’s roles during remote English teaching at SMA N 1 Tegallalang. This research used qualitative research as a method of research. This study collected data through an observation sheet and interview guide with the subjects of the study were two English teachers at SMA N 1 Tegallalang. The result of the study showed both teachers in SMA N Tegallalang already played their roles effectively in conducting the learning activity during remote teaching, both english teachers already implemented eight types teachers’ roles based on Harmer’s theory namely the role of a controller, organizer, assessor, prompter, participant, resource, tutor, and observer.